PERSEPSI PETANI TENTANG KEBIJAKAN PEMERINTAH DAERAH DALAM UPAYA PENGEMBANGAN AGRIBISNIS SAYURAN - Awaludin Sofwanto; Basita Ginting Sugihen; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The regional government policies on vegetables agribusiness development is carried out through agropolitan area development program. The aims of this study are : (1) To get informations on perception of vegetables farmer’s towards the regional government policies in the efforts of vegetables agribusiness development, (2) To get informations on the vegetables farmer’s efforts to increase vegetables agribusiness through agropolitan area development program, and (3) To analyze the correlation of farmer’s perception towards the regional government policies in the efforts of vegetables agribusiness development with the farmer’s efforts to increase vegetables agribusiness. The method of this study is using descriptive correlation. Some important results of this study are : (1) The vegetables farmer’s perception towards the regional government policies in the efforts of vegetables agribusiness development is high, (2) Vegetables farmer’s effort to increase vegetables agribusiness is high, and (3) There is significant correlation between vegetables farmer’s perception and the efforts of the vegetables farmer’s to increase vegetables agribusiness, such as : partnership with the entrepreneurs, on-farm management, and marketing management. The supporting sub-system merit such as : the micro financial institutions, agricultural education and training, agricultural extention, faciliting of regional governments to provide market places at main market in Jakarta should be increased.